Concentrations and fluxes of biogenic volatile organic compounds above a Mediterranean macchia ecosystem in western Italy - Davison, B.; Taipale, R.; Langford, B.; Misztal, P.; Fares, S.; Matteucci, G.; Loreto, F.; Cape, J. N.; Rinne, J.; Hewitt, C. N. (BIOGEOSCIENCES, 2009)
Emission rates and concentrations of biogenic volatile organic compounds (BVOCs) were measured at a Mediterranean coastal site at Castelporziano, approximately 25 km south-west of Rome, between 7 May and 3 June 2007, as part of the ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions. Concentrations and emission rates were measured using the disjunct eddy covariance (DEC) method utilizing three different proton transfer reaction mass spectrometers (PTR-MS) so allowing a comparison between the instruments. The high resolution data from the PTR-MS instruments considerably enhances the original BEMA measurements of the mid 1990s. Depending on the measurement period, the volume mixing ratios were in the range 1.6-3.5 ppbv for methanol, 0.44-1.3 ppbv for acetaldehyde, 0.96-2.1 ppbv for acetone, 0.10-0.14 ppbv for isoprene, and 0.13-0.30 ppbv for monoterpenes. A diurnal cycle in mixing ratios was apparent with daytime maxima for methanol, acetaldehyde, acetone, and isoprene. The fluxes ranged from 370-440 mu g m(-2) h(-1) for methanol, 180-360 mu g m(-2) h(-1) for acetaldehyde, 180-450 mu g m(-2) h(-1) for acetone, 71-290 mu g m(-2) h(-1) for isoprene, and 240-860 mu g m(-2) h(-1) for monoterpenes. From the measured flux data (7 May-3 June) an average basal emission rate for the Macchia vegetation was calculated of 430 mu g m(-2) h(-1) for isoprene and 1100 mu g m(-2) h(-1) for monoterpenes.
APSAPSThe following values have no corresponding Zotero field: pub-location: BAHNHOFSALLEE 1E, GOTTINGEN, 37081, GERMANY publisher: COPERNICUS GESELLSCHAFT MBH
Keywords: BVOCS; Emission rates; Mediterranean; Monoterpenes